Biomechanical Evaluation of Carpal Kinematics during Simulated Wrist Motion - Stoesser, Helen; Padmore, Clare E.; Nishiwaki, Masao; Gammon, Braden; Langohr, G. Daniel G.; Johnson, James A. (Journal of Wrist Surgery, 2017)
Background Flexion and extension of the wrist is achieved primarily at the radiocarpal and midcarpal joints. Carpal kinematics have been investigated, although there remains no consensus regarding the relative contribution of each bone to wrist motion.Purpose To determine the kinematics of the scaphoid, lunate, and capitate during unconstrained simulated wrist flexion/extension and to examine the effect of motion direction on the contribution of each bone.Materials and Methods Seven cadaveric upper extremities were tested in a passive wrist simulator with 10N tone loads applied to the wrist flexors/extensors. Scaphoid, lunate, and capitate kinematics were captured using optical tracking and analyzed with respect to the radius.Results Scaphoid and lunate motion correlated linearly with wrist motion (R2 = 0.99, 0.97). In extension, the scaphoid and lunate extended 83 ± 19% and 37 ± 18% relative to total wrist extension (p = 0.03, 0.001), respectively. In flexion, the scaphoid and lunate flexed 95 ± 20% and 70 ± 12% relative to total wrist flexion (p = 1.0,0.01) , respectively. The lunate rotated 46 ± 25% less than the capitate and 35 ± 31% less than the scaphoid. The intercarpal motion between the scaphoid and lunate was 25 ± 17% of wrist flexion.Conclusion The scaphoid, lunate, and capitate move synergistically throughout planar wrist motion. The scaphoid and lunate contributed at a greater degree during flexion, suggesting that the radiocarpal joint plays a more critical role in wrist flexion.Clinical Relevance The large magnitude of differential rotation between the scaphoid and lunate may be responsible for the high incidence of scapholunate ligament injuries. An understanding of normal carpal kinematics may assist in positioning carpal bones during partial wrist fusions and in developing more durable wrist arthroplasty designs.
Keywords: carpal bone; kinematics; wrist; scaphoid; lunate